2018
DOI: 10.1039/c8nj04945a
|View full text |Cite
|
Sign up to set email alerts
|

A lithium-modified zirconium-based metal organic framework (UiO-66) for efficient CO2 adsorption

Abstract: The adsorption mechanism of carbon dioxide (CO2) on Li/UiO-66 was studied by an in situ DRIFTS study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…531 eV, which corresponds to the binding energy of Li–O bonds. 62 It could be concluded that the doped Li + ions did interact with the 1,4-benzenedicarboxylic acid ligand (i.e., exchange the carboxylate protons) and form lithium alkoxide (i.e., lithium carboxylate group). Besides, S atoms with weak negative charges might also interact with the positively charged surface of the UiO-66 framework to further intensify the chemical adsorption.…”
Section: Results and Discussionmentioning
confidence: 99%
“…531 eV, which corresponds to the binding energy of Li–O bonds. 62 It could be concluded that the doped Li + ions did interact with the 1,4-benzenedicarboxylic acid ligand (i.e., exchange the carboxylate protons) and form lithium alkoxide (i.e., lithium carboxylate group). Besides, S atoms with weak negative charges might also interact with the positively charged surface of the UiO-66 framework to further intensify the chemical adsorption.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Additionally, we compared the oxygen XPS of Zr-UiO-66 with the Ho-MOFs (Figure S10). In the case of the Zr MOF, a peak appears at lower binding energy that corresponds to the bridging oxygen in the cluster. This peak is not present in the Ho-MOFs.…”
mentioning
confidence: 99%
“…Particularly, capture and separation methods using solid adsorbents are significant for CO 2 removal. 42,43 Numerous studies have manifested that the adsorbents with considerable ultra-micropores have great advantages for CO 2 adsorption. 44,45 Therefore, CO 2 adsorptions were conducted to measure the promising application of ACFs.…”
Section: Resultsmentioning
confidence: 99%